Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2147/jaa.s123547
|View full text |Cite
|
Sign up to set email alerts
|

Technical and clinical validation of an environmental exposure unit for ragweed

Abstract: BackgroundAllergic rhinitis is a common condition, with ragweed pollen one of the more prevalent aeroallergens. Environmental exposure units such as the Allergen BioCube® are valuable models for clinical allergy studies. A study was conducted to validate the Allergen BioCube for uniform ragweed pollen concentrations and clinically relevant sign and symptom responses to ragweed exposure.MethodsRagweed pollen concentrations were measured on 3 consecutive days in the Allergen BioCube and verified by Rotorod colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Spatial and temporal uniformity of allergen concentrations was verified with continuous laser particle counter measurements every 10 minutes whenever the unit was in use. Prior to this study, technical validation of the BioCube was performed using Rotorod collection and laser particle counts to ensure reproducibility of consistent and uniform ragweed pollen concentration in the BioCube 8. Prior clinical validation of the BioCube for ragweed pollen was also conducted; mean TNSS increased by 4.96 units from pre- to post-BioCube ragweed pollen exposure 8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial and temporal uniformity of allergen concentrations was verified with continuous laser particle counter measurements every 10 minutes whenever the unit was in use. Prior to this study, technical validation of the BioCube was performed using Rotorod collection and laser particle counts to ensure reproducibility of consistent and uniform ragweed pollen concentration in the BioCube 8. Prior clinical validation of the BioCube for ragweed pollen was also conducted; mean TNSS increased by 4.96 units from pre- to post-BioCube ragweed pollen exposure 8.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental exposure units (EEUs), first developed in the 1980s, allow for allergen specificity, control over antigen exposure levels, temperature, and air quality, and provide an accurate way of tracking self-reported and physician-observed symptoms for determining response to medication. The Allergen BioCube ® (ABC ® ) is an EEU that has been technically and clinically validated for both Timothy-grass7 and ragweed8 exposures.…”
Section: Introductionmentioning
confidence: 99%
“…A ragweed pollen concentration of 4,000±400 grains/m 3 (Ambrosia artemesiifolia) was used, similar to that used in other EEUs and peak environmental levels, and is capable of producing AR symptoms that are high enough for assessment of therapeutic treatment effi cacy [9][10][11][12] Spatial and temporal uniformity of allergen concentrations was verifi ed with continuous laser particle counter measurements every 10 minutes whenever the unit was in use. Prior to this study, technical validation of the BioCube was performed using Rotorod collection and laser particle counts to ensure reproducibility of consistent and uniform ragweed pollen concentration in the BioCube [8]. Prior clinical validation of the BioCube for ragweed pollen was also conducted; mean TNSS increased by 4.96 units from pre-to post-Biocube ragweed pollen exposure [8].…”
Section: Allergen Biocube®mentioning
confidence: 99%
“…Environmental exposure units (EEUs), fi rst developed in the 1980s are allow for allergen specifi city, control over antigen exposure levels, temperature, and air quality, and provide an accurate way of tracking self-reported and physician-observed symptoms for determining response to medication. The Allergen BioCube ® (ABC) is an EEU that has been technically and clinically validated for both Timothy [7] and ragweed [8], exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Timothy grass is native to Europe and is widely available in the U.S. as horse feed and lawn grass. The Allergen BioCube has also been validated for ragweed and dust mites , used in drug efficacy studies , and shown to induce AR symptomatology similar to the natural environment .…”
Section: Introductionmentioning
confidence: 99%